2006
DOI: 10.1007/s10764-006-9055-y
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in Populations of Microcebus murinus in Madagascar: Resource Seasonality or Bergmann's Rule?

Abstract: Gray mouse lemurs (Microcebus murinus) occur in western Madagascar from the evergreen littoral rain forests at the southern tip of the island to the seasonal dry deciduous forests of the west and northwest. The wide geographic distribution allows researchers to investigate whether ecogeographic variations reflect adaptations to ambient temperatures, as a proxy for constraints of thermoregulation, or to rainfall, as a proxy of food availability. We compared body mass, number of litters/yr, and longevity for 3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 31 publications
2
76
0
5
Order By: Relevance
“…As expected, the estimated lifespans of wild and captive M. murinus differ substantially: captive males live on average twice as long and females 50% longer than their wild counterparts. Such variation reflects highly plastic life histories that may have helped the species to adapt to the gradient of ambient temperatures found within its natural geographical distribution, and contribute to the proposed pace-of-life variation found across this range [69]. Our results concur with previous studies [39,40] that have found longer lifespan and lower AS rates in captivity than in nature.…”
Section: (D) Lifespan Determination In Captivity and Naturesupporting
confidence: 89%
“…As expected, the estimated lifespans of wild and captive M. murinus differ substantially: captive males live on average twice as long and females 50% longer than their wild counterparts. Such variation reflects highly plastic life histories that may have helped the species to adapt to the gradient of ambient temperatures found within its natural geographical distribution, and contribute to the proposed pace-of-life variation found across this range [69]. Our results concur with previous studies [39,40] that have found longer lifespan and lower AS rates in captivity than in nature.…”
Section: (D) Lifespan Determination In Captivity and Naturesupporting
confidence: 89%
“…Ongoing work from the past two decades has shown conclusively that although the morphological differences among species of mouse lemur can be subtle, their genetic and ecological differences are consistent with an evolutionary radiation that presently contains 24 described species (25,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46), with the basal diversification occurring as long ago as 9-10 Ma (47,48). Several studies have shown strong support for three deep lineages, one that contains M. murinus plus Microcebus griseorufus, another deeply diverged lineage represented by Microcebus ravelobensis, Microcebus danfossi, and Microcebus bongolavensis, and a third lineage that comprises all other mouse lemur species, including strong support for a distal subclade containing M. berthae, Microcebus rufus, and Microcebus myoxinus (41,43,44,49).…”
Section: Why Mouse Lemurs?mentioning
confidence: 88%
“…Extreme phenotypic plasticity is common among vertebrates that have evolved in unstable, energetically restrictive environments, such as those exposed to ENSO climatic anomalies (Canale and Henry, 2010). Under natural conditions, grey mouse lemurs are faced with harsher energetic constraints than in the laboratory; wild animals weigh 40% less than captive ones in the mid-winter (Lahann et al, 2006), food availability is lower and foraging is less efficient and exposes starving animals to predation. The lack of chronic stress (cf.…”
Section: Discussionmentioning
confidence: 99%